2022
DOI: 10.1021/acsaelm.2c00617
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Classification of Nanoinclusions of Composites for Thermoelectric Applications

Abstract: Thermoelectric composites are known for their enhanced power conversion performance via interfacial engineering and intensified mechanical, structural, and thermal properties. However, the selection of these nanoinclusions, for example, their type, size effect, volume fraction, distribution uniformity, coherency with host, carrier dynamics, and physical stability, plays a crucial role in modifying the host material thermoelectric properties. In this Review, we classify the nanoinclusions into five types: carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…Several theoretical and experimental studies have suggested new horizons for improving the thermoelectric properties by phonon and carrier engineering using nanoparticle (NP)-containing nanocomposite materials. ,, In fact, it was suggested that using soft magnetic, typically Fe-based, NPs dispersed in a semiconductor matrix would (i) reduce the thermal conductivity by inserting defects which combined with a Kondo-like effect can increase phonons scattering, (ii) increase the Seebeck coefficient by electron filtering at the metal/semiconductor interface, and (iii) increase the electrical conductivity by modulation doping at the metal/semiconductor interfaces due to the difference in work functions between matrix and NPs …”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and experimental studies have suggested new horizons for improving the thermoelectric properties by phonon and carrier engineering using nanoparticle (NP)-containing nanocomposite materials. ,, In fact, it was suggested that using soft magnetic, typically Fe-based, NPs dispersed in a semiconductor matrix would (i) reduce the thermal conductivity by inserting defects which combined with a Kondo-like effect can increase phonons scattering, (ii) increase the Seebeck coefficient by electron filtering at the metal/semiconductor interface, and (iii) increase the electrical conductivity by modulation doping at the metal/semiconductor interfaces due to the difference in work functions between matrix and NPs …”
Section: Introductionmentioning
confidence: 99%
“…One effective strategy for decoupling these properties involves the manipulation of nanoscale crystallinity and integration of nanostructures into the parent material. This results in the creation of distinctive multiphase structures designed to modify carrier transport. The presence of a multiphase interface disrupts the heat-carrying phonon movement due to varying thermal transport properties across different lattices, especially at the nanoscale where electron and phonon mean free paths differ significantly. A nanoscale phase with a coherent interface is essential for inducing long-wavelength phonon scattering while preserving the mobility of charge carriers. , The application of such multiphase nanocomposites facilitates synchronized modulation of electron and phonon transport by establishing unique heterojunctions at the interface between the parent matrix and the guest phase …”
Section: Introductionmentioning
confidence: 99%
“…[24] Indium antimonide (InSb) intermetallic as a nanoinclusions can improve the thermoelectric efficiency of materials and enhance the material's ZT simultaneously. [25][26][27][28][29][30][31][32][33] Semiconducting InSb nanoinclusions are added in both ex situ and in situ manner. Ex situ processing route has advantages in terms of homogeneous distribution, eliminating unwanted secondary phase formations, and controlled particle size in maximizing the interfacial boundary region.…”
Section: Introductionmentioning
confidence: 99%
“…Ex situ processing route has advantages in terms of homogeneous distribution, eliminating unwanted secondary phase formations, and controlled particle size in maximizing the interfacial boundary region. [25,28,30] Huang et al [26] demonstrated that 3 mol% InSb nanoinclusions in the Cu 12 Sb 4 S 13 matrix enhanced the thermopower via carrier energy filtering and degraded thermal conductivity via phonon scattering for maximized thermoelectric performance. Ghosh et al [27] showed that ex-situ InSb nanoinclusions reduced the CoSb 4 matrix conductivity while improving the thermopower and reducing the thermal conductivity for overall improvement in thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%